Exception and governmentality in the critique of sovereignty. (June 2016) - Burles, Regan
This article investigates the relation between exception and governmentality in the critique of sovereignty. It argues that the problem of sovereignty is not only expressed between the accounts of sovereignty that exception and governmentality articulate, but also within each of those accounts. Taking Michel Foucault and Carl Schmitt as the paradigmatic theorists of governmentality and exception, respectively, this article engages in close readings of the texts in which these concepts are most thoroughly elaborated: Security, Territory, Population and Political Theology. These readings demonstrate that the spatiotemporal expression of the problem of sovereignty within exception and governmentality renders these concepts indistinguishable from one another in terms of their relation to the boundaries of political order. Schmitt and Foucault's accounts of sovereignty should thus not be read as opposites, but as expressions of the limits of modern political authority. Efforts to develop a critique of sovereignty through typologies of exception or governmentality are bound to reinstantiate the spatiotemporal limits expressed by the principle of state sovereignty.